Negotiating Sexuality: Indonesian Female Audience towards Pornographic Media Content - Mashita Phitaloka Fandia Purwaningtyas; Cheryl Kanza Athallia Wibowo (IKAT: The Indonesian Journal of Southeast Asian Studies, 2022)
As one topic deemed controversial in Indonesia, pornography is mainly discussed for its effect on teenagers as it is explicitly segmented for adult audiences. Nevertheless, it remains problematized when it comes to female audiences as sexual desires only belong to men according to the normativity of Indonesian society. This condition stereotypes female as not a “good woman” if they happened to watch porn.  Engaging with the theory of pornography as sexual empowerment for women and applying new ethnographic method, this paper examines how Indonesian female audiences perceive pornographic media content and how it impacts their sexuality as a woman who lives in Indonesian patriarchal society. The study finds that women, on one side, are highly aware that they, too, have sexual desires just the same as their male counterparts. On the other side, they are also highly concerned about how people around them judge women who like sex or watch porn in particular; hence, it affects their sexual expression in their daily life. Furthermore, watching porn has made them negotiate their sexuality as women to try to make sense of their sexual fantasy and reality.